CHAOS BASED CRYPTOGRAPHY AND RECTANGULAR SHAPE BASED STEGANOGRAPHY TECHNIQUE USING LSB - S, Aiswarya; R, Gomathi (Malaysian Journal of Computer Science, 2023)
Multimedia means text, image, audio or video file and transferring multimedia files through the internet are noticeable one. Multimedia securing techniques are additionally used to protect the file. Securing multimedia image file is difficult by using formal encryption techniques such as AES, RSA because of high correlation between pixels. For encryption, chaotic map with XOR function is used and to provide double protection, steganography technique is used. After the encryption, encrypted image is hidden into the cover image file using LSB-steganography technique. For that, from the cover image, the rectangular positioned pixel values are selected and the encrypted image values are hidden into the selected rectangular positioned pixel locations of the cover file. Embedded image i.e., stego image is transmitted to the recipient through the internet and the reversal process is carried over at the retriever side. The performance of this proposed algorithm is analyzed by using many numerical measures such as NPCR, UACI and PSNR. These values are calculated and compared with existing methods. The obtained average NPCR, UACI and PSNR values are 99.8004%, 37.6773% and 46.41 respectively. From these statistical values, compared to existing methods, the projected work provides better result. Correlation analysis is also performed and the values are compared between the secret image and the chaotic map encrypted image. From the comparison, it is clear that the chaotic map based image encryption and steganography method provides more security and robustness in the wireless secret image transmission.